2007
DOI: 10.1038/ncpneph0573
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury, hyperosmolality and metabolic acidosis associated with lorazepam

Abstract: Discontinuation of lorazepam infusion, administration of fomepizole, hemodialysis for five consecutive days, hemodynamic support, and follow-up of serum osmolality as a measure of propylene glycol decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Propylene glycol toxicity is well described after prolonged dosing of infusions, especially in subjects with renal failure (3). Our subject developed a severe lactic acidosis from propylene glycol toxicity after a 10-hour infusion of 1.2 g. His serum propylene glycol concentration was among the highest ever reported, and his lactic acidosis was temporally related to his propylene glycol overdose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propylene glycol toxicity is well described after prolonged dosing of infusions, especially in subjects with renal failure (3). Our subject developed a severe lactic acidosis from propylene glycol toxicity after a 10-hour infusion of 1.2 g. His serum propylene glycol concentration was among the highest ever reported, and his lactic acidosis was temporally related to his propylene glycol overdose.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient responded to fomepizole and hemodialysis, the standard treatments for toxic alcohol poisoning. Previous reports described the use of fomepizole for propylene glycol poisoning following prolonged infusion (3, 4). Fomepizole acts by inhibiting alcohol dehydrogenase, the first step in metabolism of propylene glycol.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, one patient had a propylene glycol level of 58 mg/dl with no associated renal failure (Bledsoe and Kramer, 2008). It has been suggested that propylene glycol decreases renal clearance by saturating the proximal tubule [Speth et al 1987;Zar et al 2007]. A propylene glycol level was available only in one patient, but four other patients required hemodialysis for acute renal failure with metabolic abnormalities or volume overload.…”
Section: Discussionmentioning
confidence: 99%
“…Acute phase proteins such as CRP [2],[3] and cytokines [4] are elevated markedly in association with infection and inflammation. During this process, local acidosis occurs due to massive infiltration of neutrophils and macrophages [5] to the site of infection, which subsequently, activates the respiratory burst [6],[7] in many infection-inflammation related diseases such as trauma-induced infection [8], acute renal failure [9], and intra-abdominal infection [10]. These pathological conditions can decrease the pH to as low as 5.5–7.0 [11].…”
Section: Introductionmentioning
confidence: 99%